„Zwykłe” potrzeby „zwyczajnych” mężczyzn czy fantazje „zboczeńców”? Formy aktywności seksualnej klientów z perspektywy kobiet świadczących usługi seksualne - Ślęzak, Izabela (Instytut Socjologii Uniwersytetu Wrocławskiego, 2019)
The subject of this article embraces the forms of sexual activity which, according to female sex workers, are undertaken by their clients during commercial meetings. The paper presents theoretical considerations regarding the role of male clients and their reasons for getting sex services. The results of studies demonstrating the women’s reports on the forms of activity expected by the clients will also be presented, as well as studies on the forms of activity that the women actually decide to provide will be referred to. I will also demonstrate the ways in which female sex workers define and redefine the forms of activity expected by the clients, considering them as ‘normal’ or not.
Keywords: prostitution; sex services; clients’ sexual needs; forms of sexual activity